2022
DOI: 10.1186/s13053-022-00232-2
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of germline pathogenic variants using a targeted next generation sequencing panel and genotype-phenotype correlations in patients with suspected hereditary breast cancer at an academic medical centre in Pakistan

Abstract: Background Breast cancer is the most common malignancy in women, affecting over 1.5 million women every year, which accounts for the highest number of cancer-related deaths in women globally. Hereditary breast cancer (HBC), an important subset of breast cancer, accounts for 5–10% of total cases. However, in Low Middle-Income Countries (LMICs), the population-specific risk of HBC in different ethnicities and the correlation with certain clinical characteristics remain unexplored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
(74 reference statements)
2
6
1
Order By: Relevance
“…Consistent with results from other countries in our region, we found that 60% had a positive family history of BRCA1/2-related cancers, with the majority having firstdegree affected relatives (70.2%); also, predominant cancer identified among them was BC, followed by gynaecological malignancies [8,16,19,21]. Iranian study also concurs with our results of positive family history and early age at BC diagnosis and correlates it to an increased mutation detection rate [19].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with results from other countries in our region, we found that 60% had a positive family history of BRCA1/2-related cancers, with the majority having firstdegree affected relatives (70.2%); also, predominant cancer identified among them was BC, followed by gynaecological malignancies [8,16,19,21]. Iranian study also concurs with our results of positive family history and early age at BC diagnosis and correlates it to an increased mutation detection rate [19].…”
Section: Discussionsupporting
confidence: 92%
“…We found that the overall positivity of high penetrance BC genes ( BRCA1/2 and P /LP) was 20.12%; however, a study from this region showed an overall positivity as 22% [8]. Also, 73.7% were BRCA1 /2 positive and 25.2% had P /LP variants, which in contrast to the same study was 55% and 45% for BRCA1 /2 and P /LP variants, respectively [8].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Germ-line mutations in the BRCA1/2 genes predispose women to HOBC. HBOC patients in the Pakistani population have a higher positivity rate of BRCA1/2 variants in their gene pool [24] with BRCA 1 mutations being a significant contributor to the high prevalence of BC in Pakistan (found in approximately 12 % of women with early-onset BC) [24] , [25] , [26] , [27] , [28] , [29] . A BRCA 1 mutation was seen in our patient as well.…”
Section: Discussionmentioning
confidence: 99%